Understanding networks in rural Cambodian farming communities and how they influence antibiotic use: A mixed methods study. - Jane Mingjie Lim; Sokchea Huy; Ty Chhay; Borin Khieu; Li Yang Hsu; Clarence C Tam (Public Library of Science (PLoS), 2023)
Biosecurity and preventive animal health services in Cambodian smallholder backyard farming systems are often limited, leading to an over-reliance on antibiotics. However, data on factors influencing antibiotic use in these settings are lacking. We conducted a study in two rural Cambodian farming communities to investigate how social and contextual influences affect both human and animal antibiotic use behaviours. Data were collected in three phases: a baseline household census to enumerate village residents, a social network survey to understand village-level social ties, and in-depth interviews to elicit information about the influence of social ties on their decision-making processes. Primary outcome measures included knowledge, attitudes and practices surrounding antibiotic use, and awareness of issues relating to antibiotic resistance. Participants commonly accessed antibiotics or learned animal antibiotic use practices through village-level informal sources such as pharmacies or animal health workers. While most participants reported not using antibiotics for animal growth promotion or illness prevention, misconceptions surrounding both antibiotic effectiveness and resistance were common. Social networks capturing informal, work-related and health-related social ties showed that familial connections and geographic proximity were of primary importance for information sharing. Using exponential random graph models, we demonstrated that familial ties, and closer geographic and geodesic distance, were associated with similarity in overall antibiotic knowledge and attitudes. The informal private sector plays a major role in provision of antibiotics and antibiotic-related information in backyard farming communities, but such information is maintained within close social groups. This demonstrates the importance of engaging village-level informal sources in the provision of antibiotic-related information for both human and animal health, as well as in potential interventions to encourage appropriate antibiotic behaviours in lower-resourced settings.